Endoscopic Procedures in Colon and Rectum 2011
DOI: 10.5772/23321
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Colonoscopy in Understanding Inflammatory Mucosal Damage in Patients with Ulcerative Colitis and Predicting Clinical Response to Adsorptive Leucocytapheresis as a Non-Pharmacologic Treatment Intervention

Abstract: Endoscopic Procedures in Colon and Rectum 82by diverse environmental factors (2). From here on, we shall focus only on UC. The severity of UC is often presented by clinical activity index (CAI). Another, but complementary parameter is endoscopic activity index, not used in this chapter. Colonoscope, the gastroenterologist's eye and arms in modern timesColonoscopy is a revolutionary development in gastroenterology, now days like both arm and eyes for specialist gastroenterologists that can reach the inside of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In a subsequent study, Suzuki, et al [27] reported that all patients with a short duration of UC (about 3 months), and first episode cases readily responded to GMA, while all of the 8 GMA non-responders in that study had a very long duration of UC together with a long history of exposure to multiple conventional medications. The observations by Suzuki, et al [9,27] were independently confirmed by Tanaka and colleagues in much larger cohorts of UC patients [16,17,25]. …”
Section: Discussionmentioning
confidence: 79%
“…In a subsequent study, Suzuki, et al [27] reported that all patients with a short duration of UC (about 3 months), and first episode cases readily responded to GMA, while all of the 8 GMA non-responders in that study had a very long duration of UC together with a long history of exposure to multiple conventional medications. The observations by Suzuki, et al [9,27] were independently confirmed by Tanaka and colleagues in much larger cohorts of UC patients [16,17,25]. …”
Section: Discussionmentioning
confidence: 79%